Privacy-Preserving Public Auditing for Shared Data in the Cloud (International Journal of Engineering and Computer Science, 2015)
—With cloud storage services, it is commonplace for data to be not only stored in the cloud, but also shared acrossmultiple users. However, public auditing for such shared data — while preserving identity privacy — remains to be an openchallenge. In this paper, we propose the first privacy-preserving mechanism th at allows public auditing on shared data stored inthe cloud. In particular, we exploit ring signatures to compute the verification information needed to audit the integrity of shareddata. With our mechanism, the identity of the signer on each block in shared data is kept private from a third party auditor (TPA),who is still able to publicly verify the integrity of shared data without retrieving the entire file. Our experimental resultsdemonstrate the effectiveness and efficiency of our proposed mechanism when auditing shared data.